FACTORS AFFECTING THE ACHIEVEMENT OF THE INTEGRITY ZONE PREDICATE FOR A CLEAN AND SERVING BUREAUCRACY (WBBM) IN THE OFFICE OF THE PEKANBARU CITY LAND AGENCY - Bima Setia Budi Nila; Rodi Wahyudi (Indonesian Journal of Social Sciences, Policy and Politics, 2024)
This research aims to describe what factors influence the achievement of the Clean and Serving Bureaucratic Regional Integrity Zone (WBBM) Predicate at the Pekanbaru City Land Agency Office. Data collection techniques using observation, interviews, and documentation. Clean and Serving Bureaucratic Area (WBBM) is a predicate aimed at a work union that has accumulated most of the criteria for the improvement process in the leverage components to create an accountable government and excellent service as regulated in the Minister of State Apparatus Empowerment and Bureaucratic Reform Regulation Number 52 of the Year 2014. To achieve the goal of a Clean and Serving Bureaucratic Area (WBBM), the quality of development and management of integrity zones in work units must be improved. The bureaucratic reform program must be immediately implemented in work units. In a government agency environment, integrity in serving the public must be built. Government agencies are given the title of Integrity Zone (IZ) for the realization of Corruption Free Areas (WBK) and Clean Serving Bureaucratic Areas (WBBM) using bureaucratic reform, especially related to reducing corruption and improving the quality of public services. The results of this research concluded that to achieve the Predicate for a Clean and Serving Bureaucratic Area, there needs to be a collective will from all stakeholders who agree, from leadership to members/employees, they must have the commitment to give their best to get the Predicate for a Clean and Serving Bureaucratic Area (WBBM).